Penerapan multiplicative congruential random number generator pada objek game dalam game 3D “Letters Hijaiyah” - Abdul Syukur, Mohamad Arif; Wijayanto, Rivaldi Tri; Hidayat, Fakhar Muhammad; Nugroho, Fresy; Fadila, Juniardi Nur (Maliki Interdisciplinary Journal, 2024)
This study tries to design a game by applying artificial intelligence Multiplicative Congruential Random Number Generator. Random Number Generator (RNG) is a program for generating an irregular sequence of numbers or symbols. In this study, the Random Number Generator used is the Multiplicative Congruential Random Number Generator (MCRNG) on the Hijaiyah letter object Game to produce objects that appear randomly and irregularly, so that players will not easily choose objects. The use of this generator is intended so that players get a challenge in choosing hijaiyah objects whose objects come out randomly. The result of this research is a fun educational-based 3D game by applying the Congruential Multiplicative Random Number Generating Algorithm so that hijaiyah letter objects appear randomly and players can choose hijaiyah letters according to the commands from the system. So that the games made will not make players bored to play this game and players indirectly carry out learning activities about hijaiyah letters.